Questionnaire Development for TQM Implementation in the Manufacturing Industry - Khan, Zohaib; Yusof , Yusri; Ahmad, MD Fauzi (Journal of Advanced Mechanical Engineering Applications, 2024)
The goal of this article is to create a road map for manufacturing organizations with ISO 9001 certification to follow as they adopt Total Quality Management (TQM) successfully. While ISO 9001-certified organizations are better prepared to adopt TQM, no formal framework has been created to help them do so. Thus, after a review of the literature and expert review meetings, the eight primary critical success factors (CSFs) and twenty-four sub-CSFs of effective TQM implementation were identified for this study. Then, a questionnaire survey was created and sent to participants working at 75 manufacturing organizations in Pakistan in order to uncover the application level variations of these CSFs. Out of the 75 manufacturing enterprises that are members of the Pakistan Quality Association (PQA), 16 were chosen. After receiving forty completed questionnaires, the survey data was subjected to a t-test analysis. The findings showed that the most notable distinctions between these businesses were in the following areas: employee education regarding quality awareness; employee training regarding quality management techniques and resources; quality data pertaining to products supplied by suppliers; and internal customer satisfaction measurement. As a result, a roadmap based on the disclosed disparities was suggested. To implement this roadmap, ISO-certified organizations must first educate staff members about quality awareness, teach them how to use quality management techniques and resources, gather quality data about supplier-provided goods, and gauge internal customer satisfaction before advancing to total quality management (TQM).